2015
DOI: 10.1080/13607863.2015.1008985
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationships between visual acuity and severe depressive symptoms in older adults: the Salisbury Eye Evaluation study

Abstract: Objectives To assess the longitudinal relationship between visual acuity (VA) and depressive symptoms (DS) among older adults. Methods A population-based sample of 2,520 white and black individuals aged 65–84 years in 1993–1995 were assessed at baseline and at two, six, eight years later. Presenting and best-corrected visual acuity were assessed using ETDRS chart. Depressive symptoms were assessed using the Severe Depression subscale of GHQ-28. Latent Growth Curve models estimated visual acuity and depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Visual impairment was found to be associated with depression over time. Previous longitudinal studies reported con icting results: some found an association between visual impairment and the development of depression (13,(60)(61)(62)(63)(64)(65), while others did not (66,67). We provide additional evidence based on a large sample and longitudinal follow-up supporting the hypothesis that visual impairment predicts depression.…”
Section: Discussionsupporting
confidence: 51%
“…Visual impairment was found to be associated with depression over time. Previous longitudinal studies reported con icting results: some found an association between visual impairment and the development of depression (13,(60)(61)(62)(63)(64)(65), while others did not (66,67). We provide additional evidence based on a large sample and longitudinal follow-up supporting the hypothesis that visual impairment predicts depression.…”
Section: Discussionsupporting
confidence: 51%
“…Stress and mental illness may even predispose to sensory impairment. [35][36][37] Social isolation might also reduce opportunity to a. Total effect is the combined estimated direct effect of sensory impairment on CIS-R score + indirect effect mediated by SFQ score; the indirect effect is the estimated effect of sensory impairment on CIS-R score via effect on SFQ score; and the direct effect is the estimated direct effect of sensory impairment on CIS-R score (not via SQF score).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Visual impairment (VI) is a devastating disability worldwide [ 1 7 ] and has been reported to be linked with functional limitations [ 8 ], falls [ 9 ], depression [ 10 ], cognitive function [ 11 ], and mortality [ 12 , 13 ]. The health burden associated with VI has been estimated to be heavier than hypertension, diabetes, obesity, and hyperlipidemia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%